The Use of Catheter Mount Will Result in More Reliable Carbon Dioxide Monitoring under Fluid Exposing Conditions. (1st July 2019) - Cho, Yongil; Kim, Wonhee; Lim, Tae Ho; Choi, Hyuk Joong; Oh, Jaehoon; Kang, Bossng; Kim, Youjin; Kim, In Young
Abstract : Introduction . Capnometer can be readily malfunctioned by fluid exposure during treatment of critically ill patients. This study aimed to determine whether placing capnometer distant from the endotracheal tube by connecting direct connect catheter mount (DCCM) is effective in yielding reliable end-tidal carbon dioxide (ETCO2 ) by reducing capnometer malfunctioning caused by water exposure. Methods . In 25 healthy adults, a prospective, open label, crossover study was conducted to examine the effect of DCCM in mainstream and microstream capnometers under water exposing conditions. The primary endpoint was the comparison of ETCO2 between proximal DCCM (pDCCM) and distal DCCM (dDCCM). Results . For mainstream capnometers, mean ETCO2 was significantly ( p < 0.001) higher in dDCCM compared to pDCCM under water exposing conditions (29.5 vs. 19.0 with 5 ml; 33.8 vs. 21.2 with 10 ml; mmHg). Likewise, for microstream capnometers, ETCO2 was greatly higher ( p < 0.001) in dDCCM compared to pDCCM (30.5 vs. 13.9 with 5 ml; 29.9 vs.11.4 with 10 mL; mmHg). ETCO2 measured by dDCCM was reliable in microstream settings, whereas it was unreliable in mainstream (correlation coefficient 0.88 vs. 0.27). Conclusions . Application of DCCM onto the capnometer setting seems to be effective in reducing capnometer malfunctioning under fluid exposing conditions, which is obvious in microstream capnometer by producing more reliable ETCO2 .